Presupposition in the Movie "Pitch Perfect" - Adra Mufidah Paradieta (Lexicon, 2014)
This research attempts to classify the type and analyze the function of presupposition in the movie Pitch Perfect. According to Yule’s theory of presupposition type (1996), 114 presuppositions are found: existential triggered by definite description and possessive construction (22.06%), factive triggered by factiveverb/predicate; temporal clause; the word thank,lexical triggered by implicative predicate; change of state verb; iterative; cleft sentence; comparisons; adverbs; superlative construction (24.83%), structural triggered by WH-question (11.72%), non-factive (7.58%), and counterfactual if- clause (7.58%). Based Jakobson’s theory (1960), there are 4 functions of presupposition in the movie: referential (35.10%), emotive (42.10%), conative (10.52%), and phatic (12.28%).